Electrical data of 10W, 40W, 80W, and 250W photovoltaic modules under the aging condition: Tested by a Solar Manufacturer Company in Bangladesh - Ahmed Al Mansur; Md. Ruhul Amin; Md. Imamul Islam; ASM Shihavuddin (Data in Brief, 2023)
The health monitoring system of photovoltaic modules throughout their lifespan is an important research topic. The dataset of aged PV modules is required to investigate the performance of the aged PV array for simulation work. Different aging factors are responsible for decreasing the output power of aged PV modules and increasing the degradation rate. In addition, mismatch power losses are increases with the nonuniformity of aged PV modules due to different aging factors. In this work, four datasets of 10W, 40W, 80W, and 250W PV modules are collected under nonuniform aging conditions. Each dataset contains forty modules with a four-year aged average. The average deviation of each electrical parameter of the PV modules can be calculated from this data. Moreover, a correlation can be developed between the average deviation of electrical parameters and mismatch power loss in PV array modules under early aging conditions.